Covid -19 Pandemic and Impact on Teaching and Learning of Technical College Students in Ekiti State, Nigeria - Ogunmilade Johnson O. (Budapest International Research and Critics University, 2023)
The study examined the covid-19 pandemic and impact on teaching and learning of technical college students in Ekiti State, Nigeria. The population was (3,425) for 2018/19 academic session. The descriptive research of the survey design was employed. Validated instrument of covid-19 pandemic and impact on teaching and learning of technical college students questionnaire (CPITLTCQ) was employed to gather the necessary data. The research instrument was validated using face and content validity. The questionnaire contains 15 items in the 4-point worth scale and information about respondents. The questionnaire were properly filled and coded into SPSS. Cronbach alpha was used to obtain 0.64 reliability coefficient showing that the instrument was stable. Mean and standard deviation was used to analyze the data collected for the study. Based on the findings, it was recommended among others, that Government and other relevant educational bodies and stakeholders should provide stable electricity, quality and standard internet connection. Training and seminars should be organized for the teachers to be updated, remote learning challenges should be looked into so that technical education can be improved in Ekiti State.